Non-Hodgkin lymphoma of oral cavity; a case report - Z. Tohidast Ekrad (Tehran University of Medical Sciences, 1994)
Malignant lymphoma is the neoplastic transformation of Cells, mostly originating from lymphoid tissues. Malignant lymphoma has two major subtypes: Hodgkin and non-Hodgkin lymphoma. Malignant lymphoma is the most common neoplasm in 3rd and 4th decades of life and more than two third of affected patients presented painless peripheral lymphadenopathy. Involvement of waldeyer's ring, epitrochlear and mesenteric lymph nodes is more likely in non-Hodgkin lymphoma. Approximately 20% of patients with non-Hodgkin lymphoma have mediastinal adenopathy. Most often, these patients may suffer from persistent cough, chest discomfort or maybe referred without any complaint and just with an abnormal chest radiograph.